Controllable Singlet–Triplet Energy Splitting of Graphene Quantum Dots through Oxidation: From Phosphorescence to TADF. Issue 31 (14th June 2020) - Park, Minsu; Kim, Hyung Suk; Yoon, Hyewon; Kim, Jin; Lee, Sukki; Yoo, Seunghyup; Jeon, Seokwoo
Abstract: Long‐lived afterglow emissions, such as room‐temperature phosphorescence (RTP) and thermally activated delayed fluorescence (TADF), are beneficial in the fields of displays, bioimaging, and data security. However, it is challenging to realize a single material that simultaneously exhibits both RTP and TADF properties with their relative strengths varied in a controlled manner. Herein, a new design approach is reported to control singlet–triplet energy splitting (∆ E ST ) in graphene quantum dots (GQD)/graphene oxide quantum dots (GOQDs) by varying the ratio of oxygenated carbon to sp 2 carbon (γOC ). It is demonstrated that ∆ E ST decreases from 0.365 to 0.123 eV as γOC increases from 4.63% to 59.6%, which in turn induces a dramatic transition from RTP to TADF. Matrix‐assisted stabilization of triplet excited states provides ultralong lifetimes to both RTP and TADF. Embedded in boron oxynitride, the low oxidized (4.63%) GQD exhibits an RTP lifetime (τ T avg ) of 783 ms, and the highly oxidized (59.6%) GOQD exhibits a TADF lifetime (τ DF avg ) of 125 ms. Furthermore, the long‐lived RTP and TADF materials enable the first demonstration of anticounterfeiting and multilevel information security using GQD. These results will open up a new approach to the engineering of singlet–triplet splitting in GQD for controlled realization of smart multimodal afterglow materials. Abstract : Oxidation control of graphene quantum dots can tune the singlet–triplet energy splitting, which induces a dramatic afterglow transition from phosphorescence to thermally activated delayed fluorescence. Matrix‐assisted stabilization of triplet excited states provides ultralong lifetimes to such afterglow emissions. A new design approach for engineering singlet–triplet energy splitting through facile molecular manipulation will enable the realization of smart multimodal afterglow materials.